Oxymatrine Attenuates Dopaminergic Neuronal Damage and Microglia-Mediated Neuroinflammation Through Cathepsin D-Dependent HMGB1/TLR4/NF-κB Pathway in Parkinson’s Disease - Gan, Ping; Ding, Lidong; Hang, Guihua; Xia, Qiaofang; Huang, Zhimei; Ye, Xing; Qian, Xiaojuan (Frontiers in Pharmacology, 2020)
Oxymatrine (OMT), a natural quinoxaline alkaloid extracted from the root of Sophora ﬂavescens, presents amounts of pharmacological properties including immunomodulation, anti-inflammation, anti-oxidation and anti-virus. Recent studies tend to focus on its effects on neuroinflammation and neuroprotection in Parkinson’s disease (PD) due to its profound anti-inﬂammatory effect. In this study, the neuroprotective and anti-neuroinflammatory effects of OMT were investigated in 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-stimulated mice and 1-methyl-4-phenylpyridinium (MPP+)-induced mice primary microglia. Additionally, mice primary neuron-microglia co-cultures and primary microglia infected with Cathepsin D (CathD)-overexpressed lentivirus were used to clarify whether the neuroprotective effect of OMT was through a CathD-dependent pathway. Results showed that OMT dose-dependently alleviated MPTP-induced motor deficits and conferred significant dopamine (DA) neuroprotection against MPTP/MPP+-induced neurotoxicity. In addition, OMT inhibited MPTP/MPP+-induced microglia activation and the pro-inflammatory cytokines release. Further, OMT down-regulated the expression of CathD, and inhibited the activation of the HMGB1/TLR4 signaling pathway as well as the nuclear translocation of NF-κB both in vivo and in vitro. It is worth noting that overexpression of CathD reversed OMT-targeted inhibition of HMGB1/TLR4/NF-κB signaling and OMT-produced neuroprotection in reconstituted neuron-microglia co-cultures. Our findings indicated that OMT conferred DA neuroprotection and attenuated microglial-mediated neuroinflammation through CathD-dependent inhibition of HMGB1/TLR4/NF-κB signaling pathway. Our study supports a potential role for OMT in ameliorating PD, and proposes that OMT may be useful in the treatment of PD.